2019
DOI: 10.13189/ujer.2019.070225
|View full text |Cite
|
Sign up to set email alerts
|

Using Flipped Learning to Improve Scientific Research Skills of Teacher Candidates

Abstract: The primary aim of this study was to investigate the effect of a scientific research methods course delivered through flipped learning on teacher candidates' attitudes towards scientific research and the course, and examine the teacher candidates' and instructors' experience in the process. The convergent parallel design was adopted in the study, and the participants were 102 elementary education teacher candidates taking the scientific research methods course at a Turkish university. Throughout the 12-week co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
11
0
2
Order By: Relevance
“…This corroborates previous experiences in motivating research students by means of non-traditional methodologies (flipped classroom, collaborative and cooperative practice, etc. ), with good consequences for the research skills of students [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corroborates previous experiences in motivating research students by means of non-traditional methodologies (flipped classroom, collaborative and cooperative practice, etc. ), with good consequences for the research skills of students [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, research and innovation training is also an important aspect of the development of a teacher candidate [17][18][19][20]. However, some teaching candidates feel that their education did not prepare them to work as teacher-researchers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Demo (2006) highlights the importance of preparing teachers to be innovative with their methods of teaching scientific methodology, considering students' learning process and construction of their citizenship. Teachers must receive theoretical and practical training to understand the nature of scientific research and learn to deal with the problems encountered in the learning process (Bastürk, 2017;Sever et al, 2019). Maia (2008) and Moreira and Caleffe (2011) agree that appropriate strategies combined with the choice of teaching content and procedures may lead individuals to acquire habits and attitudes that benefit their professional and personal lives.…”
Section: Teaching Practice In Learning Scientific Methodologymentioning
confidence: 99%
“…Furthermore, the learning time is not spent on memorizing the materials, but is spent on a building a deeper understanding and analysis (Rui et al, 2017). Moreover, the absence of the need to convey information to the whole class allows the teacher to pay more attention to individual students or small groups in the cases where they have problems with understanding the material (Sever et al, 2019). ) and the study revealed that FLM engaged the students effectively and it led them to be better prepared for the 21st century learning and workenvironments" (Bormann, 2014, p. III).…”
Section: Literature Reviewmentioning
confidence: 99%